Problematika Hukum dan Alternatif Penyelesaiannya Bagi Konsumen Pengguna Jasa Aplikasi Gojek dan Grabcar sebagai Angkutan Berbasis On Line - Dwi Handayani; Muhammad Ilyas (ADHAPER: Jurnal Hukum Acara Perdata, 2018)
Various legal issues that have surfaced to date cannot be separated from the development of information technology that has mastered the world map. People as consumers really need fast and cheap transportation services to transport people or goods to meet their daily needs. The presence of the Gojek and GrabCar application services is one of the solutions needed by the community at this time, but there is no legal umbrella that regulates people’s transportation services for motorbikes or motorbikes and the transportation of people or passengers to Gocar or Grabcar in private cars, causing various legal issues in its application. Legal issues that arise, are forms of legal protection for consumer users and dispute resolution due to default by one of the parties. The research method is empirical research by processing primary and secondary data, which are then analyzed qualitatively. Conclusions on the results of the discussion: a form of legal protection for consumers and drivers in the form of compensation or assistance in the amount of ﬁve to 10 million rupiahs for guaranteed protection for hospital fees and in the event of accidents and life insurance guarantees from AXA Group. The procedure for resolving a default by a Gojek-GrabCar application provider as a result of private law or civil relations is that the application service user as a party to the agreement can choose to take legal action (litigation) or peace/mediation/conciliation (non-litigation).